A new xyelotomid (Hymenoptera) from the Middle Jurassic of China displaying enigmatic venational asymmetry. Issue 1 (December 2016) - Gao, Taiping; Shih, Chungkun; Engel, Michael; Ren, Dong
Abstract Background Pterygota insects typically have symmetric veins in left and right wings. For studying taxonomy and phylogeny of fossil insects, venational patterns are commonly used as diagnostic characters, in conjunction with preserved body characters. Some examples of asymmetrical venation are known among extant insects, but only a few fossil insects with asymmetric wings have been reported, among which a previously described xyelotomid of Hymenoptera, Xyelocerus diaphanous, displays an unusual, small cell of vein Rs in the left forewing, but not in the right. Results Herein we report a new sawfly of the family Xyelotomidae, Aethotoma aninomorpha gen. et sp. nov., from the late Middle Jurassic of China having a simple Sc in the forewing and Sc with two branches in the hind wing. In additional, the new specimen exhibits an enigmatic venational asymmetry. In the right forewing, crossvein 2r-rs of forms a loop, then forks into 2 long branches reaching Rs, while 2r-rs of the left forewing forks into 2 short branches reaching Rs, in contrast to a linear 2r-rs in typical fossil and extant sawflies. Conclusion Such rare asymmetrical venation found from fossil sawflies provides a glance at early occurrences of venational variability and instability, or possibly aberrational development, for insects in the late Middle Jurassic.